NONLINEAR SCIENCE ISSUES IN THE DYNAMICS OF UNSTABLE ROCK SLOPES: NEW TOOLS FOR ROCK FALL RISK ASSESSMENT AND EARLY WARNINGS - Zvelebil J.; Paluš M.; Novotná D. (My University, 2006)
Time series of displacement data from unstable rock slopes contain 'hidden' information about the dynamics of slope failure. This information cannot be found when using the current linearly causal paradigm based on analytical methods, but is revealed when numerical and graphical methods from the toolbox of the Nonlinear Sciences are applied. The occurrence of fractal patterns, which suggests a qualitative difference between intrinsic slope movement dynamics of time series from the near-to-equilibrium and the far-from-equilibrium dynamical states of slope failure systems, is an example of such a 'hidden', diagnostically important indicator. It helps to identify the stage of immediate danger of rock fall occurrence, just in time to launch an efficient early warning. Phase portrait and correlograms of time series proved to be suitable for earlier revelation of transitions from the near-to-equilibrium to the far-from-equilibrium dynamical states, as well as for helping to distinguish between intrinsic slope movement dynamics and climatically driven reversible deformation activity. © The Geological Society of London 2006.